The Social Dynamics of Spirituality and Youthfulness: A Social Interplay Between Disposition and Process - Jonathan James O. Canete; Digvijay Pandey (CV. Literasi Indonesia, 2020)
Issues and topics concerning spirituality is not new in the social sphere. Many great thinkers in the fields of philosophy and theology have tried to excavate the richness of the topic. Though not new a topic, there are still various avenues in the sphere of spirituality that need to be examined and discovered through intellectual abstraction and practical observation. The relevance of spirituality cannot be contained in a specific era nor time frame or even in established social structures because it deals with people and their disposition toward life and a certain desire in their very being for transcendence. In other words, spirituality is all about a person’s attitude towards life and a quest for an existential meaning behind every experience that might be of unequalled value or significance. Hence, spirituality is not static but dynamic in its very being, for as long as man desires to go beyond his present state of being and moves into another manner of existence, spirituality is evident; it manifests itself in that affinity for self-transcendence. The term youth, alternatively, also speaks of a dynamic progressive or regressive movement of the self, outside of its present state of being. This study, therefore, is an attempt to phenomenological interpret and appropriate the concept of spirituality as an unfolding of existence on the concept of youthfulness not just an ordinary process in the life of a person wherein one becomes open for self-improvement or self-transcendence.